How would you prove that the generating function of $\binom{2n}{n}$ is $\frac{1}{\sqrt{1-4x}}$?

More precisely, prove that( for $|x|<\frac{1}{4}$ ):


Background: I was trying to solve $$S=\sum^{\infty}_{n=0}\frac{(2n+1)!}{8^n(n!)^2}=\sum^{\infty}_{n=0}\frac{(2n+1)}{8^n}\binom{2n}{n}$$ Which if we let $f(x)$ be the generating function in question, would be simply $$f(x)+2xf'(x)$$ With $x=\frac{1}{8}$. Is there a simple proof of the first identity? Wikipedia states it without a proper reference (the reference provided states it without proof). Is there an easier way of calculating $S$? (which is $\sqrt{8}$, by the way)

  • $\begingroup$ There is a proof by Lagrange inversion at this MSE link. $\endgroup$ Dec 12 '14 at 1:21
  • $\begingroup$ @MarkoRiedel Hm, that's a more general case, but it linked to this. Also, sorry for the wrong previous title, copy-and-paste error. So, close because dupe? $\endgroup$
    – chubakueno
    Dec 12 '14 at 1:27

Here is a simple derivation of the generating function: start with $$ (1+x)^{-1/2} = \sum_k \binom{-1/2}{k}x^k.$$ Now, \begin{align*} \binom{-1/2}{k} &= \frac{\left(-\frac{1}{2}\right)\left(-\frac{3}{2}\right)\left(\cdots\right)\left(-\frac{1}{2}-k+1\right)}{k!} \\ &= (-1)^k \frac{1\cdot 3\cdot 5\cdots (2k-1)}{2^k k!} \\ &= (-1)^k \frac{(2k)!}{2^k2^kk!k!} \\ &= (-1)^k 2^{-2k}\binom{2k}{k}. \end{align*} Finally replace $x$ by $-4x$ in the binomial expansion, giving $$ (1-4x)^{-1/2} = \sum_k (-1)^k 2^{-2k}\binom{2k}{k}\cdot (-4x)^k = \sum_k \binom{2k}{k}x^k.$$


Use the binomial theorem. Then $(1-4x)^{-{1 \over 2}} = \sum_{k=0}^\infty \binom{-{1 \over 2}}{k}(-1)^k 4^k x^k$.

$\binom{-{1 \over 2}}{k}(-1)^k 4^k = {\prod_{j=0}^{k-1}((-4)(-{1 \over 2}-j)) \over k!} = {\prod_{j=0}^{k-1}(2(1+2i)) \over k!} = {2^k (2k)!\over 2^kk! k!} = \binom{2k}{k}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.